Impact of upslope impervious surface to run-on/runoff relationship [electronic resource] - Nor Suhaila Rahim, 1989-; Muhammad Nassir (2012)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2012